2019
DOI: 10.7759/cureus.4572
|View full text |Cite
|
Sign up to set email alerts
|

Re-expansion of Osteoporotic Compression Fractures Using Bilateral SpineJack Implants: Early Clinical Experience and Biomechanical Considerations

Abstract: Thoraco-lumbar osteoporotic compression fractures have a higher incidence of continued collapse with development of deformity and progression to vertebra plana when untreated and even after vertebral augmentation (VA) or balloon kyphoplasty (BKP). Even when there is the restoration of height and improvement in angulation, multiple long-term follow-up series have repeatedly documented that over time, many patients lose the initial height correction and in a smaller group the vertebral body re-collapses leading … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…In cases planning to use a SJ device, CT scan provides more accurate measurements of the pedicle width in axial view, which is used for sizing of the closed implant diameter and determining overall depth within the fractured vertebral body [ 7 , 8 , 13 ]. CT also gives detailed information in any fracture lines through the endplates and posterior vertebral wall that may be related to increased risk of cement leakage either into the disk space or epidural space [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In cases planning to use a SJ device, CT scan provides more accurate measurements of the pedicle width in axial view, which is used for sizing of the closed implant diameter and determining overall depth within the fractured vertebral body [ 7 , 8 , 13 ]. CT also gives detailed information in any fracture lines through the endplates and posterior vertebral wall that may be related to increased risk of cement leakage either into the disk space or epidural space [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Over the last 10 years, the evolution of third-generation intravertebral implants demonstrates that implants often can provide significant height correction beyond what occurs with balloon kyphoplasty and that this correction can be maintained over one or more years. Follow-up studies have also shown that these permanently expanded implants are associated with statistically less adjacent level fractures [ 7 , 8 ]. VP cases were specifically excluded from the early SpineJack® (SJ) studies (Stryker Corp, Kalamazoo, Michigan, USA) [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These titanium implants could also be used as a structural adjunct in treating fractures related to destructive vertebral tumors combined with radiation or intratumoral therapy. In a 36-month follow-up study comparing BKP to SJ, clinical improvements were observed with both procedures over the three-year period, vertebral height restoration/kyphotic correction was still evident at 36 months, with a greater mean correction of anterior (10 ± 13% vs 2 ± 8% for BKP, p = 0.007) and central height (10 ± 11% vs 3 ± 7% for BKP, p = 0.034) and a larger correction of the vertebral body angle (− 5.0° ± 5.1° vs 0.4° ± 3.4°; p = 0.003) for SJ group [16-18]. The initial correction is both maximized and maintained while using less PMMA, an average of 2.5 to 3.00 cc of cement in total, leading to less risk of cement leakage (Figure 5).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the previous PEEK implants restored pressure in the affected disc associated with vertebral endplate fracture and may be related to the significant lower incidence of adjacent level fractures seen in long term SJ studies [14-15]. More recent intra-operative pre and post SJ implant studies show restoration of the adjacent superior disc pressures closer to normal which correlates with a lower incidence of adjacent level fractures compared to BKP [13,17-18].…”
Section: Discussionmentioning
confidence: 99%